Magnesium Potentiates the Vortioxetine’s Effects on Physical Performances and Biological Changes in Exercise-Induced Stress in Rats - Paula Alina Fotache; Liliana Mititelu-Tartau; Maria Bogdan; Beatrice Rozalina Buca; Liliana Lacramioara Pavel; Ana-Maria Pelin; Andreea-Daniela Meca; Cosmin-Gabriel Tartau; Gratiela Eliza Popa (Medicina, 2022)
Background and objectives: Vortioxetine (VRT) is a relatively new selective serotonin reuptake inhibitor (SSRI) antidepressant and serotonin receptor modulator, approved for the treatment of major depression and generalized anxiety disorder. Depression has been linked with psychomotor disengagement, oxidative stress burden and decreased blood levels of brain-derived neurotrophic factor (BDNF). In our study we performed the experimental investigation of VRT, magnesium and of their association on the rats’ endurance capacity, motor behavior and blood biological disturbances in rats subjected to forced exercise in treadmill test. Materials and Methods: The substances were administered orally for 14 consecutive days, as follows: group 1 (control): distilled water 0.3 mL/100 g body; group 2 (Mg): magnesium chloride 200 mg/kg body; group 3 (VRT): VRT 20 mg/kg body; group 4 (VRT+Mg): VRT 20 mg/kg body + magnesium chloride 200 mg/kg body. Magnesium was used as positive control substance with known effects in treadmill test. The consequences of VRT treatment on glucose, cortisol, BDNF and oxidative stress biomarkers (superoxide-dismutase, malondialdehyde, glutathione-peroxidase, lactate dehydrogenase) were also assessed. Results and conclusions: The use of VRT resulted in an improvement in motor capacity and an increase of the rats’ endurance to physical effort. The administration of VRT increased the serum BDNF levels and reduced the oxidative stress in rats subjected to physical effort. The association of magnesium potentiated the effects of VRT on physical performances, the antioxidant activity and the decreasing in serum stress markers in treadmill test in rats.